(untitled) (Academicia Globe: Inderscience Research, 2024)
This article presents the strengths and weaknesses of the health care models currently in use in the world, a comparative analysis of the experiences of foreign countries in this regard, and suggestions for reforming the health care sector in the public health protection system of Uzbekistan.